Teachers of English Assessment Literacy: Unveiling What They Know and Do - Soni Mirizon (Universitas Jambi, Indonesia, 2021)
Conducting assessment is one of the crucial responsibilities every teacher has to do. A teacher needs to assess his students both during and at the end of instruction; therefore he needs to have good assessment literacy in order to be able to carry out assessment successfully. This study investigated teachers’ of English assessment literacy at two different senior high schools in Palembang. This case study involved six teachers of English as participants. The data were collected using questionnaires, semi-structured interview, classroom observation, and documentation. Data obtained from questionnaires were analysed using descriptive statistics, while data obtained from the semi-structured interview were analysed using thematic analysis through coding. Data obtained from classroom observation and documents were used to verify the ones from the questionnaire and interview. The findings revealed that teachers of English were in fairly literate category of assessment literacy; not every teacher carried out formative assessment regularly; they encountered difficulties in assessing students learning due to lacked understanding in interpreting the basic competence of the curriculum which led to inappropriate indicators formulation; assessment items did not match with the formulated indicators; and lacked of variety in constructing question items for formative assessment. These difficulties are due to that they lacked of experience in constructing assessment items and lacked of formal training related to test items construction. These findings lead to the conclusion that teachers assessment literacy needs to be enhanced so that they could carry out accountable assessment to support their students learning.